Dirasah Fiqhiyyah Lihadits “Bai’atain fi Bai’ah” fi Manzur al-Iqtisad al-Islami - Daud Rasyid (Universitas Darussalam Gontor, 2013)
Hadits is one source of Islamic Law. There are contracts which are forbidden is Islamic Law. One of that forbidden contracts is two sales in one contract (bay’atayn fi bay’ahor safqatayn fi safqah). There are narrations of the Ahadith which forbids this type of contract. The paper discusses the authenticity of these narrations and its legal meaning. According to the science of Hadits that daif (weak) Hadith could not be considered as valid source of law. There are three narrations related to this topic i.e. through Abu Hurayrah, Amru ibn Shuaib and Ibn Mas’ud. The Prophet (pbh) has forbidden two sales in one contract. This Hadits is generally considered as Sahih hence some transactions which come under this type are deemed as void. Muslim scholars have different opinion with regard to the meaning of this Hadits. There are some forms of contract which are forbidden is Islamic Law such as 1. Bay’ al-ienah, 2.Bay’ al-Kali’ bil Kali’ and Bay’ al-Taqsit or Ta’jil (on deferred payment). This paper is an effort to shed the light on these types of contract referring to the opinions of Muslim intellectuals from different school of thought (Hanafite, Shafiite, Malikite and Hanbalite) with some conclusion et the end.